Effect of promising rice (Oryza sativa L.) varieties and nutrient management practices on growth, development and crop productivity in eastern Himalayas - M.N., Harish; Choudhary, Anil K.; Singh, Y.V.; Pooniya, Vijay; Das, Anup; T., Varatharajan; Babu, Subhash (Annals of Agricultural Research, 2018)
A field experiment was conducted at the Experimental Farm of ICAR-Research Complex for NorthEastern Hill Region, Barapani, Meghalaya during Kharif 2016 to study the effect of promising ricevarieties and nutrient management practices on plant growth, development, and grain and biologicalyield of lowland rice in Eastern Himalayas. The experiment was laid-out in split-plot design replicatedthrice consisting of 12 treatment combinations viz. 4 nutrient management practices [100% organic,100% inorganic (RDF), INM (50% RDF through fertilizers + remaining 50% RDF through FYM androck phosphate), and absolute control] in main-plot, and 3 promising rice varieties [Shahsarang-1,Lumpnah and Megha semi-aromatic-2] in sub-plots. The results showed that the plant height, drymatter accumulation (DMA), leaf area index (LAI), growth indices like absolute growth rate (AGR),crop growth rate (CGR), relative growth rate (RGR) and net assimilation rate (NAR) improvedconstantly with the succession of crop growth period i.e. 30 to 90 days after transplanting (DAT) aswell as at harvest. Plant height, DMA, LAI, and growth indices in rice crop were observed to beconsiderably influenced by different nutrient management practices. Among different nutrientmanagement practices, significantly higher magnitude of above parameters was found in integratednutrient management (INM) practice followed by inorganic practice, organic practice and control,respectively. Among rice varieties, Shahsarang-1 exhibited higher magnitude of above growthparameters followed by Lumpnah and Megha SA2, respectively. These rice varieties both underINM as well as under inorganic practice gave higher amount of growth parameters viz. plant height,DMA, LAI, growth indices in rice greater than their other counterparts. Grain yield was significantlyhigher (4.18 t ha–1) in INM practice followed by inorganic, organic and control treatment. The trendof grain yield was INM>inorganic>organic>control treatment, respectively. Similar trend was alsoobserved for biological yield. Among rice varieties, Shahsarang-1 produced significantly highestgrain yield (3.86 t ha–1) followed by Lumpnah (3.60 t ha–1) and Megha SA2 (3.19 t ha–1), respectively.Similar trend was also observed for biological yield. In nutshell, INM practice (50% RDF throughfertilizers + remaining 50% RDF through FYM and rock phosphate) is the best nutrient managementtechnology to harness better growth and crop productivity in eastern Himalayas. Similarly,Shahsarang-1 was the best performer in terms of growth and crop productivity over other twopromising rice varieties viz. Lumpnah and Megha SA2 in north-eastern Himalayan region.